Cellulose nanocrystal reinforced liquid natural rubber toughened unsaturated polyester: Effects of filler content and surface treatment on its morphological, thermal, mechanical, and viscoelastic properties. (5th August 2015) - Kargarzadeh, Hanieh; Sheltami, Rasha M.; Ahmad, Ishak; Abdullah, Ibrahim; Dufresne, Alain
Abstract: Cellulose nanocrystals (CNCs) isolated from kenaf bast fibers were used to reinforce unsaturated polyester resin (UPR) composites toughened with liquid natural rubber (LNR). The surface of the CNCs was modified with silane, and the effects of this treatment on the morphological, tensile, and thermal properties of the resulting composites were studied. Electron micrographs show that the CNCs are well dispersed in the UPR and the rubber phase and that the rubber particles are smaller in the nanocellulose composites. Tensile tests show that untreated CNC–LNR–UPR composites are as strong as toughened UPR. The tensile modulus increases significantly with either treated or untreated CNC content of the composites. The impact resistance of UPR increases as LNR and then CNCs are added, with the best results obtained with silane-treated CNCs. The viscoelastic behavior and the thermal resistance of the composites also improve upon addition of both treated and untreated CNCs. Graphical abstract: Highlights: Unsaturated polyester resin was modified with a liquid natural rubber. Cellulose nanocrystals were added, improving mechanical properties. Cellulose nanocrystals were modified with silane coupling agent. Cellulose nanocrystals formed a 3D interpenetrating network to toughen matrix. Desirable properties were realized by modifying additive contents.